Transparent colorless spinel microcrystalline glass and preparation and application thereof
By adjusting the oxide ratio and heat treatment temperature, the challenges of spinel microcrystalline glass in terms of drop resistance and mass production are solved, and the colorless transparent microcrystalline glass with high Young's modulus and excellent optical performance are achieved, improving the Its mass production and fall resistance are achieved.
Patent Information
- Application Number
- CN202411431633.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-02
- Publication Date
- 2025-01-10
AI Technical Summary
Existing spinel microcrystalline glasses have challenges in combining excellent transparency and mechanical properties, especially in drop resistance, and high temperature heat treatment limits its mass production and optical properties.
By adjusting the oxide ratio, such as the content of Al2O3, Li2O, Na2O, B2O3, and ZrO2, using ZrO2 as the nucleating agent, basically no TiO2 is used, and the heat treatment temperature is reduced to no more than 800°C to obtain a high Young's modulus and Transparent colorless spinel microcrystalline glass with hardness and a compressive stress layer is formed by ion exchange to improve drop resistance.
It is realized that transparent colorless spinel microcrystalline glass with excellent optical properties and high mechanical strength is prepared under low temperature heat treatment conditions, which improves its mass productionability and significantly improves its drop resistance.
Smart Images

Figure CN119285233A_ABST
Abstract
Description
[0001] This application is a divisional application of the application with application number 202211546703.5, application date December 02, 2022, and invention name “A transparent colorless spinel microcrystalline glass and its preparation and application”. Technical Field
[0002] The invention relates to a transparent microcrystalline glass, and more specifically to a transparent colorless microcrystalline glass with a zinc-magnesium spinel solid solution as a main crystal phase. Background Art
[0003] With the development and progress of materials science, many new materials have been used in the design and manufacture of smart terminal devices. Glass-ceramics have become a better choice for screen covers due to their excellent mechanical properties and excellent light transmittance. Glass-ceramics, also known as glass ceramics, is a material that precipitates specific crystals inside the glass by heat treating the substrate glass. The crystals dispersed inside the glass-ceramics enable it to have physical properties that cannot be obtained in ordinary glass. For example, the mechanical strength such as Young's modulus and shear toughness are significantly enhanced, and the tolerance to acidic and alkaline liquids is significantly improved.
[0004] Zinc spinel (ZnAl 2 O 4 ) is a cubic mineral. According to the Mohs hardness scale, the spinel hardness is 7.5-8 and the measured density is 4.38-4.60 g / cm 3 At ambient pressure, the Young's modulus of zinc spinel is about 290GPa, the shear modulus is about 146GPa, and the refractive index is 1.79-1.80. However, zinc spinel crystals can easily make glass devitrified, making it difficult to prepare transparent microcrystalline glass, and are not suitable for preparing screen covers. 2 O 4 ) crystals are the main crystalline phase. Although transparent microcrystalline glass can be prepared, the Young's modulus and shear modulus of magnesium spinel crystals are not as good as those of zinc spinel. Zinc spinel and magnesium spinel form zinc-magnesium spinel solid solution (Zn, Mg)Al 2 O 4 , the properties of the solid solution are similar to those of zinc spinel (ZnAl 2 O 4 ) are almost the same, and transparent glass-ceramics can be made with zinc-magnesium spinel solid solution as the main crystal phase. Compared with transparent glass-ceramics with magnesium spinel as the main crystal phase, transparent spinel glass-ceramics with zinc-magnesium spinel solid solution as the main crystal phase has higher Young's modulus and shear modulus, which can bring higher mechanical strength to the glass-ceramics material.
[0005] Patent application US5968857A discloses a glass-ceramic with spinel as the main crystal phase, which is expressed in weight percentage based on oxides and has a composition of 45-65% SiO 2 , 14~28%Al 2 O 3 , 4~13% ZnO, 0~8% MgO, 0~10% TiO 2 , 0~6%ZrO 2 , 0-8% BaO, 0-15% CsO, ZnO+MgO combination is greater than or equal to about 8, and TiO 2 +ZrO 2 The combination is greater than about 4, and the obtained microcrystalline glass has an optical property of visible light transmittance reaching 85%. In the one (or two) stage heat treatment, the upper limit of the temperature of the growing crystal is preferably in the range of 875-1050°C.
[0006] Patent application CN104478219A discloses a method of preparing a 56-62wt% SiO 2 , 19~23wt%Al 2 O 3 , 6~15wt% ZnO, 2~6.5wt% MgO, 2~6wt% TiO 2 , 2~7wt%ZrO 2 The basic composition is spinel glass-ceramics, the crystallization treatment temperature is 880℃~1050℃, and the average grain size is 30~100nm.
[0007] Patent application CN111018354A discloses a low melting temperature glass-ceramic, which is composed of SiO 2 :48~55mol%Al 2 O 3 :14~17mol%, ZnO: 2~12mol%, MgO: 8~16mol%, TiO 2 :0.5~4.5mol%ZrO 2 :0.1~3mol%Sb 2 O 3 :0.5~1mol%Na 2 O: 2-12 mol%; two-step heat treatment is performed at 650-750°C and 800-870°C to obtain a spinel glass-ceramic with a visible light transmittance of not less than 80%. Summary of the invention
[0008] The inventors have found that the currently disclosed spinel glass-ceramics generally cannot be chemically strengthened and toughened, resulting in poor toughness and drop resistance despite the characteristics of high hardness, especially when the thickness is small (≤1mm), the brittleness is more obvious, and it is not suitable for making electronic cover glass that requires high impact resistance.
[0009] For electronic cover glass, it is necessary to have excellent deep stress characteristics, such as higher DOL_0 and CT_AV, especially higher DOL_0, in order to achieve good drop resistance. In order to achieve excellent deep stress characteristics, the common method used in this field is to chemically strengthen the substrate glass and obtain higher DOL_0 and CT_AV through ion exchange. In order to meet the requirements of ion exchange chemical strengthening, it is necessary to add a certain amount of alkali metal oxides, such as Li 2 O and Na 2 O.
[0010] However, after further research, the inventors found that: as the Li 2 O and Na 2 As the amount of O added increases, the solid solution of zircon-magnesium spinel is precipitated in the glass, and some crystals that affect the optical properties of the microcrystalline glass are also precipitated, such as β-quartz (SiO 2 ), β-quartz solid solution (MgAl 2 Si 3 O 10 ), β-spodumene, etc. The precipitation of these impurity phase crystals can easily cause the prepared microcrystalline glass to become foggy or even devitrified, and it is often difficult to obtain the ideal transparent and colorless spinel microcrystalline glass. How to make spinel microcrystalline glass meet the stress characteristic requirements of cover glass while maintaining excellent optical properties is a technical problem that the inventors need to solve urgently.
[0011] The inventors also found that during the preparation of existing spinel glass-ceramics, the upper limit of the heat treatment temperature, such as the crystallization temperature during the two-step heat treatment, is generally higher than 800°C, mostly above 850°C, or even 900°C and above. Such a high heat treatment temperature places high demands on the heat treatment kiln, which is not conducive to energy conservation and carbon reduction, resulting in great restrictions on the mass production of spinel glass-ceramics.
[0012] In addition, most of the existing zinc-magnesium spinel transparent glass-ceramics use a composite nucleating agent (TiO 2 +ZrO 2 ) to promote the formation of zinc-magnesium spinel glass-ceramics. 2 As a nucleating agent, it is very easy to cause glass coloring; only ZrO 2 When used as a nucleating agent, it is very easy to form ZrO 2Precipitation causes the glass to turn white in some areas and the overall uniformity to deteriorate.
[0013] The inventors have conducted a lot of experiments and research to find out the problems found in the above research and development process. 2 O 3 , Li 2 O,Na 2 O, B 2 O 3 、ZrO 2 By using the same content, a colorless and transparent spinel glass-ceramic with a heat treatment temperature below 800°C and high transparency can be obtained. The mass production of the colorless and transparent spinel glass-ceramic has been greatly improved. The glass-ceramic can be chemically strengthened to produce a strengthened glass-ceramic with excellent deep stress characteristics.
[0014] Specifically, the present invention provides the following technical solutions:
[0015] 1. A glass-ceramic, characterized in that it contains a zinc-magnesium spinel solid solution (Zn, Mg)Al as a main crystal phase 2 O 4 and subcrystalline tetragonal ZrO 2 (tetragonal zirconium oxide); in terms of molar percentage of oxides, the glass-ceramics contains the following oxide components:
[0016]
[0017]
[0018] Furthermore, the glass-ceramics substantially does not contain TiO 2 ; “Substantially free” here means that TiO 2 added or dosed to glass, but may be present in very small quantities as impurities or contaminants;
[0019] The oxide component content of the microcrystalline glass satisfies the following relationship:
[0020] (1)Al 2 O 3 / (MgO+ZnO)=1.40~2.00;
[0021] (2) (K 2 O+Li 2 O+Na 2 O+B 2 O 3 ) / (SiO 2 +Al 2 O 3 )=0.10~0.20;
[0022] In the above relationship, each oxide represents the mole percentage content of the oxide in the component.
[0023] 2. The microcrystalline glass according to technical solution 1, wherein SiO 2 The molar percentage is 38.50% to 48.50%; and / or Al 2 O 3 The molar percentage of is 25.00% to 29.00%; and / or the molar percentage of MgO is 4.50% to 7.50%; and / or the molar percentage of ZnO is 8.50% to 13.50%; and / or the molar percentage of ZrO is 2 The molar percentage is 3.50% to 4.50%; and / or Li 2 The molar percentage of O is 3.00% to 7.80%.
[0024] 3. The glass-ceramic according to technical solution 1 or 2, which is obtained by using ZrO 2 Prepared as a nucleating agent.
[0025] 4. The glass-ceramic according to any one of technical solutions 1 to 3, wherein the glass-ceramic further contains oxide components in the following proportions, measured in molar percentage of oxides:
[0026]
[0027] 5. The glass-ceramic according to any one of technical solutions 1 to 4, wherein the content of the oxide component is expressed in mol%, and satisfies at least one of the relations (3), (4) and (5):
[0028] (3)Al 2 O 3 / SiO 2 =0.50~0.80;
[0029] (4)Li 2 O / (K 2 O+Li 2 O+Na 2 O) = 0.25 ~ 0.85;
[0030] (5)Li 2 O+Na 2 O≥7.00mol%.
[0031] 6. The microcrystalline glass according to any one of technical solutions 1-5, wherein the microcrystalline glass is obtained by heat treatment at a temperature not exceeding 800°C.
[0032] 7. The glass-ceramics according to any one of technical solutions 1 to 6, wherein the weight ratio of the crystal phase of the glass-ceramics to the glass-ceramics is 25.0 to 45.0 wt%, preferably 30.0 to 45.0 wt%, and more preferably 32.0-40.0 wt%.
[0033] 8. The microcrystalline glass according to any one of technical solutions 1 to 7, wherein the average grain size of the microcrystalline glass is 3.0-30.0 nm, preferably 3.0-10.0 nm, more preferably 5.0-6.5 nm, and further preferably 5.2-6.5 nm.
[0034] 9. The microcrystalline glass according to any one of technical solutions 1-8, wherein the Young's modulus of the microcrystalline glass is ≥110 GPa; preferably, 130 GPa≥Young's modulus≥110 GPa; more preferably, 130 GPa≥Young's modulus>114 GPa.
[0035] 10. The glass-ceramic according to any one of technical solutions 1 to 9, wherein when the thickness is 0.7 mm, the glass-ceramic has the following transmission color coordinates in the CIELAB color space:
[0036] a* = -0.15-0.15, preferably -0.15 to -0.03; and
[0037] b*=0.30-0.90, preferably 0.60 to 0.85; this is for D65 light source in SCI mode.
[0038] 11. The microcrystalline glass according to any one of technical solutions 1 to 10, wherein when the thickness is 0.7 mm, the transmittance of the microcrystalline glass under light of 550 nm wavelength is above 85.0%, and preferably the transmittance is 88.0%-95.0%; when the thickness is 0.7 mm, the transmittance of the microcrystalline glass under light of 360 nm wavelength is above 70.0%.
[0039] 12. The microcrystalline glass according to any one of technical solutions 1 to 11, wherein the microcrystalline glass comprises a compressive stress layer formed by ion exchange.
[0040] 13. The microcrystalline glass according to technical solution 12, wherein the microcrystalline glass comprises a compressive stress layer, the depth of the compressive stress layer DOL_0 ≥ 0.14t, t is the thickness of the microcrystalline glass, preferably 0.20t ≥ DOL_0 ≥ 0.15t.
[0041] 14. The microcrystalline glass according to technical solution 12 or 13, wherein |CT_AV| of the microcrystalline glass is ≥40.0MPa, preferably 80.0MPa≥|CT_AV|≥40.0MPa.
[0042] 15. The glass-ceramics according to any one of technical solutions 12-14, wherein the glass-ceramics is obtained by chemical strengthening treatment in a salt bath containing potassium salt and / or sodium salt, wherein the salt bath contains 0-1wt% of lithium salt; preferably, it is obtained by chemical strengthening treatment in a mixed salt bath of sodium salt and potassium salt or a pure sodium salt bath, and further preferably, it is obtained by chemical strengthening treatment in a mixed salt bath of sodium nitrate and potassium nitrate or a sodium nitrate salt bath.
[0043] 16. The microcrystalline glass according to technical solution 15, wherein in the mixed salt bath of sodium nitrate and potassium nitrate, the concentration of sodium nitrate is 30-70wt%.
[0044] 17. The glass-ceramic according to any one of technical solutions 12 to 16, wherein the Vickers hardness of the glass-ceramic is above 750 HV.
[0045] And / or, the fracture toughness of the glass-ceramics is 1.200 MPa·m 1 / 2 Above, preferably 1.400 MPa·m 1 / 2 More preferably, 1.500 MPa·m 1 / 2 above.
[0046] 18. The microcrystalline glass according to any one of technical solutions 12-17, wherein, at a thickness of 0.7 mm, the microcrystalline glass is subjected to a sandpaper drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the microcrystalline glass is greater than or equal to 0.80 m, and preferably the average sandpaper drop resistance height is 1.00-1.60 m.
[0047] 19. The method for preparing glass-ceramics according to any one of technical solutions 1 to 10, characterized in that it comprises the following steps:
[0048] (1) Preparation of substrate glass: The substrate glass contains the following oxide components in molar percentage: SiO 2 :38.00%~50.00%,Al 2 O 3 :25.00%~30.00%,
[0049] MgO: 4.00%~8.00%, ZnO: 8.00%~14.00%, ZrO 2 :3.00%~5.00%,
[0050] Li 2 O: 3.00% to 8.00% (8.00 mol %) is not taken;
[0051] Furthermore, the substrate glass does not contain TiO 2 ;
[0052] Wherein, the oxide component content of the substrate glass satisfies the following relationship:
[0053] Al 2 O 3 / (MgO+ZnO)=1.40~2.00;
[0054] (K 2 O+Li 2 O+Na 2 O+B 2 O 3 ) / (SiO 2 +Al 2 O 3 )=0.10~0.20;
[0055] (2) Preparation of glass-ceramics: The substrate glass obtained in step (1) is heat-treated to obtain the glass-ceramics as described in any one of technical solutions 1 to 10.
[0056] 20. The preparation method according to technical solution 19, wherein in step (2), the heat treatment includes nucleation treatment and crystallization treatment performed sequentially; the temperature of the nucleation treatment is 650-850°C, preferably 650-750°C, and the time is 0-72h, preferably 0-24h; the temperature of the crystallization treatment is 700-1000°C, preferably 700-800°C, and the time is 0.1-72h, preferably 0.1-24h.
[0057] 21. The preparation method according to technical solution 19 or 20, wherein the substrate glass further contains oxide components in the following proportions, measured by molar percentage of oxides: Na 2 O: 0%~6.00%, K 2 O: 0%~3.00%, B 2 O 3 :0%~6.00%, BaO: 0%~4.00%, Y 2 O 3 :0%~2.00%,La 2 O 3 : 0% to 2.00%; and / or, the oxide component content is measured in mol%, satisfying at least one of the following relationships: Al 2 O 3 / SiO 2 =0.50~0.80; Li 2 O / (K 2 O+Li 2 O+Na 2 O)=0.25~0.85;Li 2 O+Na 2O≥7.00mol%.
[0058] 22. The preparation method according to any one of technical solutions 19-21, further comprising the following steps:
[0059] The microcrystalline glass obtained by heat treatment is subjected to chemical strengthening treatment to obtain the microcrystalline glass as described in any one of technical solutions 11-17.
[0060] 23. Glass-ceramics obtained by the preparation method described in any one of Technical Solutions 19-22.
[0061] 24. Application of the microcrystalline glass described in any one of Technical Solutions 1 to 18 or the microcrystalline glass described in Technical Solution 23 in mobile phone displays, tablet computer displays, handheld game consoles, electronic terminals, portable digital devices, vehicle central control screens, electronic whiteboard glass, smart home touch screens, vehicle windshields, aircraft windshields or aircraft windshields.
[0062] 25. A substrate glass, which can be used to prepare the glass-ceramics as described in any one of technical solutions 1 to 18, wherein the substrate glass contains the following oxide components in terms of molar percentage of oxides: SiO 2 :38.00%~50.00%,Al 2 O 3 :25.00%~30.00%, MgO:4.00%~8.00%, ZnO:8.00%~14.00%, ZrO 2 :3.00%~5.00%,Li 2 O: 3.00% to 8.00% (8.00 mol % is not taken); and the substrate glass does not contain TiO 2 ; Wherein, the oxide component content of the substrate glass satisfies the following relationship: Al 2 O 3 / (MgO+ZnO)=1.40~2.00;(K 2 O+Li 2 O+Na 2 O+B 2 O 3 )
[0063] / (SiO 2 +Al 2 O 3 )=0.10~0.20.
[0064] 26. The substrate glass according to technical solution 25 is characterized in that, in terms of molar percentage of oxides, the substrate glass further contains oxide components in the following proportions: Na 2 O: 0%~6.00%, K2 O: 0%~3.00%, B 2 O 3 :0%~6.00%, BaO: 0%~4.00%, Y 2 O 3 :0%~2.00%,La 2 O 3 : 0% to 2.00%; and / or, the oxide component content is measured in mol%, satisfying at least one of the following relationships: Al 2 O 3 / SiO 2 =0.50~0.80; Li 2 O / (K 2 O+Li 2 O+Na 2 O)=0.25~0.85;Li 2 O+Na 2 O≥7.00mol%.
[0065] In the present invention, the forming method of the substrate glass includes but is not limited to float, overflow, rolling or casting process. For example, the components are mixed evenly according to the formula, melted and formed, and then cooled and annealed to obtain the substrate glass. When preparing the substrate glass, a clarifier can be added to the substrate glass, and the clarifier is not limited to SnO 2 , Sb 2 O 3 , NaCl; based on the mass of the substrate glass, the amount of the clarifier added is 0.01wt% to 2.00wt%, preferably 0.01wt% to 1.50wt%.
[0066] The technical solution of the present invention has the following beneficial effects: the transparent colorless spinel glass-ceramics of the present invention is reasonably matched with Al 2 O 3 , Li 2 O,Na 2 O, B 2 O 3 、ZrO 2 The content of the oxides is such that the content of each oxide meets the specific relationship requirements. 2 As a nucleating agent, TiO is basically not used 2When used as a nucleating agent, a target glass-ceramic with a specific structure, good overall uniformity and high intrinsic strength can be obtained through a lower heat treatment temperature. The optimized spinel glass-ceramic formula of the present invention can significantly reduce the heat treatment temperature required to prepare the target glass-ceramic, which meets the development needs of the industry for energy conservation and carbon reduction, improves the mass production of transparent colorless spinel glass-ceramic, and ensures the excellent optical properties of glass-ceramic. At the same time, the glass-ceramic has a high Young's modulus and hardness, and the glass-ceramic can be chemically strengthened to produce a strengthened glass-ceramic with excellent drop resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 It is the DSC test curve diagram of the substrate glass D3;
[0068] Figure 2 It is the DSC test curve of the substrate glass D4;
[0069] Figure 3 is a DSC test curve diagram of substrate glass S3;
[0070] Figure 4 It is the DSC test curve diagram of the substrate glass S5;
[0071] Figure 5 This is a picture of the brick of the substrate glass D1;
[0072] Figure 6 This is the glass-ceramic sample picture corresponding to experiment number 3;
[0073] Figure 7 This is the XRD test curve of the glass-ceramics corresponding to Experiment No. 19;
[0074] Figure 8 This is the picture of the glass-ceramic sample corresponding to experiment number 18. DETAILED DESCRIPTION
[0075] The present invention aims to solve the technical problems that the transparent spinel glass-ceramics in the prior art are difficult to mass produce and that the glass-ceramics have both excellent transparency and excellent mechanical properties (especially drop resistance). By adjusting the formula composition of the glass-ceramics and exploring the specific process parameters, a transparent colorless spinel glass-ceramics is provided, which has a heat treatment temperature of less than 800°C, meets excellent optical properties, and can obtain excellent deep stress properties through chemical strengthening.
[0076] In a first aspect, the present invention provides a glass-ceramic, which satisfies:
[0077] (1) The crystal phase of the glass-ceramics of the present invention includes: zinc-magnesium spinel solid solution (Zn, Mg)Al 2 O 4and tetragonal zirconia ZrO 2 The main crystal phase is zinc-magnesium spinel solid solution (Zn, Mg)Al 2 O 4 .
[0078] (2) In terms of molar percentage of oxides, the glass-ceramics contains the following oxide components: SiO 2 :38.00%~50.00%,Al 2 O 3 :25.00%~30.00%, MgO:4.00%~8.00%, ZnO:8.00%~14.00%, ZrO 2 :3.00%~5.00%,Li 2 O: 3.00% to 8.00% (8.00 mol% is not taken).
[0079] (3) Al 2 O 3 / (MgO+ZnO)=1.40~2.00.
[0080] (4) (K 2 O+Li 2 O+Na 2 O+B 2 O 3 ) / (SiO 2 +Al 2 O 3 )=0.10~0.20.
[0081] (5) Al 2 O 3 / SiO 2 =0.50~0.80.
[0082] (6) Li 2 O / (K 2 O+Li 2 O+Na 2 O)=0.25~0.85.
[0083] (7) Li 2 O+Na 2 O≥7.00mol%.
[0084] Note: In the equations (3)-(7), the molar percentage content of each oxide is substituted into the equation for calculation.
[0085] (8) The nucleating agent is ZrO 2 , basically no TiO 2 The “substantially free” here means that TiO 2Added or dosed to glass, but may be present in very small amounts as an impurity or contaminant.
[0086] (9) When preparing the microcrystalline glass, the upper limit of the temperature for heat treatment may not exceed 800°C, that is, the microcrystalline glass can be obtained by heat treatment at a temperature not exceeding 800°C.
[0087] (10) In terms of molar percentage of oxides, the substrate glass further contains oxide components in the following proportions: Na 2 O: 0%~6.00%, K 2 O: 0%~3.00%, B 2 O 3 :0%~6.00%, BaO: 0%~4.00%, Y 2 O 3 :0%~2.00%,La 2 O 3 :0%~2.00%.
[0088] (11) Young's modulus ≥ 110 GPa, preferably, 130 GPa ≥ Young's modulus ≥ 110 GPa, more preferably, 130 GPa ≥ Young's modulus > 114 GPa.
[0089] (12) The average grain size is 3.0-30.0 nm, preferably 3.0-10.0 nm, more preferably 5.0-6.5 nm.
[0090] (13) The weight ratio of the crystal phase to the glass-ceramics is 25.0 to 45.0 wt %, preferably 30.0 to 45.0 wt %, and more preferably 32.0 to 40.0 wt %.
[0091] (14) When the thickness is 0.7 mm, the microcrystalline glass has the following transmission color coordinates in the CIELAB color space: a*=-0.15 to 0.15; and b*=0.30 to 0.90; this is for the D65 light source in the SCI mode.
[0092] (15) When the thickness is 0.7 mm, the transmittance of the microcrystalline glass under light of 550 nm wavelength is greater than 85.0%, and the preferred transmittance is 88.0%-95.0%; when the thickness is 0.7 mm, the transmittance of the microcrystalline glass under light of 360 nm wavelength is greater than 70.0%.
[0093] (16) The glass-ceramic includes a compressive stress layer formed by ion exchange; the depth of the compressive stress layer DOL_0 is greater than or equal to 0.14t, where t is the thickness of the glass-ceramic. Exemplarily, when t=0.7mm, the depth of the compressive stress layer DOL_0 of the glass-ceramic is greater than or equal to 98μm, preferably 100-140μm. The compressive stress layer extends from the surface of the glass-ceramic to the compression depth, and at the same time, a tensile stress layer is formed inside the glass-ceramic that can achieve force balance with the compressive stress layer. It should be understood that after the ion exchange process, the composition of the surface of the glass-ceramic (i.e., the compressive stress layer) may be different from the composition of the newly formed glass-ceramic (i.e., the glass-ceramic before undergoing the ion exchange process). This is because during ion exchange, a type of alkali metal ion (e.g., Li + Or Na + ) are replaced by larger alkali metal ions (e.g., Na + or K + However, in an embodiment, the composition of the glass-ceramic at the center of the depth of the glass article or near the center of the depth (ie, the tensile stress layer) will still have the composition of the just-formed glass-ceramic.
[0094] (17) When the glass-ceramics is chemically strengthened, the chemical strengthening treatment may be carried out in a salt bath of potassium salt and / or sodium salt and / or lithium salt, preferably in a mixed salt bath of sodium salt and potassium salt or in a pure sodium salt bath, and more preferably in a mixed salt bath of sodium nitrate and potassium nitrate or in a sodium nitrate bath, to obtain a glass-ceramics having an absolute value of average tensile stress |CT_AV|≥40.0MPa, preferably 80.0MPa≥|CT_AV|≥40.0MPa. When the chemical strengthening treatment is carried out in a mixed salt bath of sodium nitrate and potassium nitrate, the concentration of sodium nitrate in the mixed salt bath is preferably 30-70wt%.
[0095] (18) After chemical strengthening treatment, the Vickers hardness of the glass-ceramics is above 750 HV, and / or the fracture toughness of the glass-ceramics is 1.200 MPa·m 1 / 2 Above, preferably 1.400 MPa·m 1 / 2 More preferably, 1.500 MPa·m 1 / 2 above.
[0096] (19) At a thickness of 0.7 mm, the microcrystalline glass comprising a compressive stress layer is subjected to a sandpaper drop resistance test using 80-grit sandpaper. The average sandpaper drop resistance height of the microcrystalline glass is greater than or equal to 0.80 m, and preferably the average sandpaper drop resistance height is 1.00-1.60 m.
[0097] The transparent colorless spinel glass-ceramics of the present invention is reasonably matched with Al2 O 3 , Li 2 O,Na 2 O, B 2 O 3 、ZrO 2 The content of oxides is the same as that of Al 2 O 3 ≥25.00mol%Li 2 O = 3.00 ~ 8.00 mol% (8 mol% is not taken), use ZrO 2 As a nucleating agent, TiO is rarely used. 2 As a nucleating agent, the content of each oxide meets specific relationship requirements, such as Al 2 O 3 / (MgO+ZnO)=1.40~2.00,(K 2 O+Li 2 O+Na 2 O+B 2 O 3 ) / (SiO 2 +Al 2 O 3 )=0.10~0.20, the target glass-ceramics with a specific structure, good overall uniformity and high intrinsic strength can be obtained at a relatively low heat treatment temperature (for example, the upper limit temperature of the heat treatment does not exceed 800°C). The optimized spinel glass-ceramics formula of the present invention can significantly reduce the heat treatment temperature required to prepare the target glass-ceramics, which meets the development needs of energy conservation and carbon reduction in the industry, and realizes the preparation of transparent zinc-magnesium spinel glass-ceramics under the condition of a heat treatment temperature below 800°C, thereby improving the mass producibility of transparent spinel glass-ceramics and ensuring the excellent optical properties of glass-ceramics. At the same time, the glass-ceramics of the present invention have a high Young's modulus and hardness, and the glass-ceramics can be chemically strengthened to produce strengthened glass-ceramics with excellent drop resistance.
[0098] The substrate glass of the glass-ceramics of the present invention can be directly produced by using existing molding processes, including but not limited to the float method, rolling method, casting method and overflow method.
[0099] Oxidation effect
[0100] Li 2 O and Na 2 The increase of O content is helpful to obtain higher stress, especially excellent deep stress characteristics, and is also helpful to reduce the melting temperature and the temperature of crystal precipitation. However, excessive addition of O will lead to the precipitation of other impurities during the heat treatment process, which will reduce the transmittance of the obtained microcrystalline glass. 2O content is 3.00~8.00mol% (8.00mol% is not taken), Na 2 The O content is 0 to 6.00 mol%.
[0101] In some embodiments, the glass ceramics may include 3.00-7.90 mol%, 3.50-7.90 mol%, 4.00-7.90 mol%, 4.50-7.90 mol%, 5.00-7.90 mol%, 5.50-7.90 mol%, 6.00-7.90 mol%, 6.50-7.90 mol%, 7.00-7.90 mol%, 3.00-7.50 mol%, 3.00-7.00 mol%, 3.00-6.50 mol%, 3.00-6.00 mol%, 3.00-5.50 mol%, 3.00-5.00 mol%, 3.00-4.50 mol%, 3.00-4.00 mol%. 2 In some embodiments, the glass-ceramics may contain Li in a molar percentage of 3.00 mol%, 3.50 mol%, 4.00 mol%, 4.50 mol%, 5.00 mol%, 5.50 mol%, 6.00 mol%, 6.50 mol%, 7.00 mol%, 7.50 mol% or 7.90 mol%, or in a numerical range consisting of any two of the above specific values as endpoints. 2 O. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.
[0102] In some embodiments, the glass-ceramics may contain 0-6 mol % of Na 2 O, specifically Na 2 O may be in the range of 0.5-5.5, 0.5-5, 0.5-4.5, 0.5-4, 0.5-3.5, 0.5-3.0, 0.5-2.5, 0.5-2.0, 0.5-1.5, 0.5-1.0, etc. in molar percentage; or may be in the range of 0.5, 1.0, 1.5, 2.0, 2.5, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0 mol%, etc., or in the range of molar percentage formed by any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass having the desired properties of the present invention can be obtained.
[0103] Al 2 O 3The addition of Al can promote the precipitation of spinel, inhibit the precipitation of other impurities such as quartz ss, and increase the ion exchange rate during the strengthening process. 2 O 3 This will cause the melting difficulty of the glass to increase sharply, and the crystallization rate will be extremely fast, and devitrification will occur during the normal cooling process. 2 O 3 The content is 25.00 to 30.00 mol%. Specifically, Al 2 O 3 The molar percentage content may be 25.00, 25.50, 26.00, 26.50, 27.00, 27.50, 28.00, 28.50, 29.00, 29.50, 30.00 mol%, etc., or a molar percentage content within a numerical range consisting of any two of the above specific values as endpoints, such as a molar percentage range of 25.00-29.50, 26.00-28.50, etc. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.
[0104] MgO and ZnO, as the main components of spinel, can promote the precipitation of spinel and reduce the difficulty of melting to a certain extent. However, the addition of excessive MgO and ZnO often leads to excessive growth of spinel grains and excessively large grain sizes, making it difficult to obtain microcrystalline glass with high transparency. At the same time, the ratio of MgO and ZnO largely determines whether the sample is transparent. In the microcrystalline glass of the present invention, the MgO content is 4.00-8.00 mol%, and the ZnO content is 8.00-14.00 mol%. Specifically, the MgO content may be 4.00, 4.50, 5.00, 5.50, 6.00, 6.50, 7.00, 7.50, 8.00 mol%, etc., or may be a molar percentage content within a numerical range consisting of any two of the above specific values as endpoints, such as 4.00-7.50, 4.00-7.00, 4.00-6.50, 4.00-6.00, 4.00-5.50, 4.50-5.00, 5.00-7.50, 5.00-7.00, 5.00-6.50, 5.00-6.00, 5.00-5.50, etc. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.Specifically, the ZnO content can be 8.00, 8.50, 9.00, 9.50, 10.00, 10.50, 11.00, 11.50, 12.00, 12.50, 13.00, 13.50, 14.00 mol%, etc., or it can be a molar percentage content within a numerical range consisting of any two of the above specific values as endpoints, such as 8.00-13.50, 8.00-13.00, 8.00-12.50, 8.00-12.00, 8.00 -11.50, 8.00-11.00, 8.00-10.50, 8.00-10.00, 8.00-9.50, 8.00-9.00, 8.00-8.50, 8.50-13.50, 8.50-13.00, 8.50-12.50, 8.50-12.00, 8.50-11.50, 8.50-11.00, 8.50-10.50, 8.50-10.00, 8.50-9.50, 8.50-9.00, 9.50- 13.50, 9.50-13.00, 9.50-12.50, 9.50-12.00, 9.50-11.50, 9.50-11.00, 9.50-10.50, 9.50-10.00, 10.00-13.50, 10.00-13.00, 10.00-12.50, 10.00-12.00, 10.00-11.50, 10.50-13.50, 10.50-13.00, 10.50-12.50, 10.5 The molar percentage ranges are 0-12.00, 10.50-11.50, 10.50-11.00, 11.00-13.50, 11.00-13.00, 11.00-12.50, 11.00-12.00, 11.00-11.50, 11.50-13.50, 11.50-13.00, 11.50-12.50, 11.50-12.00, 12.00-13.50, 12.00-13.00, 12.00-12.50, etc. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.
[0105] ZrO 2 As an effective nucleating agent, ZrO 2 First precipitated from the parent phase in the form of crystals, ZrO 2 The crystal becomes the nucleus for the subsequent crystal growth. Within a certain glass composition range, ZrO 2 The content of ZrO will affect the formation of the substrate glass, the shape of the crystals in the microcrystalline glass, the type of crystals and the size of the crystals. By adjusting the composition of the substrate glass, ZrO2 The ZrO is first precipitated, and then the spinel crystal grows to achieve heat treatment. 2 The content of ZrO is 3.00 to 5.00 mol%. Specifically, ZrO 2 The content can be 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00 mol% or the like, or can be a mol% content within a numerical range consisting of any two of the above specific values as endpoints, such as 3.10-4.90, 3.20-3.80, 3.30-3.70, 3.40-3.60 or the like. Add B in an appropriate amount 2 O 3 It can greatly reduce the difficulty of glass melting and promote the precipitation of spinel, but excessive B 2 O 3 The addition of B may easily lead to opacity during heat treatment and may also lead to the precipitation of other impurity crystal phases, seriously affecting the transparency of the glass. 2 O 3 The content of B is 0 to 6.00 mol%. 2 O 3 The molar percentage content may be in the range of 0.5-5.5, 0.5-5, 0.5-4.5, 0.5-4, 0.5-3.5, 0.5-3, 0.5-2.5, 0.5-2, 0.5-1.5, 0.5-1, etc.; or may be in the range of 0.5, 1, 1.5, 2.0, 2.5, 3.5, 4, 4.5, 5.0, 5.5, 6 mol%, etc., or in the range of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass with the desired properties of the present invention can be obtained.
[0106] SiO 2 It is an oxide that forms the glass network skeleton and is used to stabilize the network structure of glass and microcrystalline glass. 2 When the content is too small, the glass tends to have a higher thermal expansion coefficient and lower thermal shock resistance; SiO 2 When the content is too high, the melting property of the glass deteriorates, or the viscosity of the molten glass increases, making it difficult to clarify the glass, making it more difficult to form the glass, reducing productivity, and prolonging the time required for crystallization of the glass. 2 The content of SiO is 38.00 to 50.00 mol%. Specifically, SiO2 It can be 38.00, 38.50, 39.00, 39.50, 40.00, 40.50, 41.00, 41.50, 41.00, 41.50, 43.00, 43.50, 44.00, 44.50, 45.00, 45.50, 46.00, 46.50, 47.00, 47.50, 48.00, 48.50, 49.00, 49.50, 50.0 0mol%, or a molar percentage content within a numerical range consisting of any two of the above specific values as endpoints, such as 38.00-49.50, 39.00-49.00, 40.00-48.00, 41.00-47.00, 42.00-46.00, 43.00-45.00, 43.00-44.00, 38.50-49.50, etc. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.
[0107] K 2 O is an oxide outside the network, due to K + Radius larger than Na + Therefore, add appropriate amount of K 2 O can reduce the crystallization tendency of glass and increase the transparency and gloss of glass. 2 When the O content is too high, the crystallization ability of the glass becomes stronger, the glass is easily devitrified, and the crystallized glass is easily broken. 2 The content of O is 0 to 3.00 mol%. 2 O may be in a molar percentage range of 0.1-3.0, 0.5-2.5, 0.5-2.0, 0.5-1.5, 0.5-1.0, 1.0-2.5, 1.0-2.0, 1.0-1.5, etc.; or may be in a molar percentage range of 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0 mol%, etc., or in a molar percentage range formed by any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges may be combined with any other ranges as long as the glass having the desired properties of the present invention can be obtained.
[0108] An appropriate amount of BaO is beneficial to reducing the viscosity of the glass, improving the melting and forming properties of the glass, and can also be used to adjust the thermal expansion coefficient and refractive index of the microcrystalline glass. In the microcrystalline glass of the present invention, the content of BaO is 0-4.00 mol%. Specifically, the molar percentage content of BaO can be 0.1-4.0, 0.5-3.5, 0.5-3.0, 0.5-2.5, 0.5-2.0, 0.5-1.5, 0.5-1.0, 1.0-3.5, 1.0-3.0, 1.0-2.5, 1.0-2.0, 1.0-1.5, 1.5-3.5, 1.5-3.0, 1.5-2.5, 1.5-2.0, etc.; it can also be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.3, 3.3, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0 mol%, or a molar percentage content within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.
[0109] The right amount of Y 2 O 3 and / or La 2 O 3 It can improve the density of the glass phase, thereby improving the overall strength of the microcrystalline glass. At the same time, it can be combined with ZrO 2 Forming a eutectic, reducing ZrO when melting in a furnace 2 The unevenness caused by precipitation. However, the excess Y 2 O 3 It will affect the precipitation of spinel crystals. In the glass-ceramics of the present invention, Y 2 O 3 The content is 0~2mol%La 2 O 3 The content is 0 to 2 mol%. 2 O 3 and La 2 O 3Each independently can be 0.1-2.0, 0.1-1.5, 0.1-1.0, 0.2-2.0, 0.2-1.5, 0.2-1.0, 0.3-2.0, 0.3-1.5, 0.3-1.0, 0.4-2.0, 0.4-1.5, 0.4-1.0, 0.5-2.0, 0.5-1.5, 0.5-1.0, 0.6-2.0, 0.6-1.5, 0.6-1.0, 0.7-2.0, 0.7-1.5, 0.7-1.0, 0.8-2. The molar percentage content in the range of 0, 0.8-1.5, 0.8-1.0, 0.9-2.0, 0.9-1.5, 0.9-1.0, etc. can also be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 mol%, etc., or the molar percentage content in the numerical range formed by any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the glass with the desired properties of the present invention can be obtained.
[0110] It is worth mentioning that the inventors found through a large number of experiments that Al 2 O 3 、ZrO 2 ,MgO,ZnO,Na 2 O.K 2 O. Li 2 O、SiO 2 The addition of SiO has different effects on the crystallization temperature. 2 It will reduce the crystallization temperature of spinel, Al 2 O 3 It will increase the crystallization temperature of spinel, etc., and the influence of each oxide on the crystallization temperature is also different. For example, the one with the greatest influence is Al 2 O 3 and SiO 2 , Li 2 O and B 2 O 3 Secondly, and so on. The inventors have rationally matched Al 2 O 3 , Li 2 O,Na 2 O, B 2 O 3 、ZrO 2 The content of oxides such as Al 2 O 3 / (MgO+ZnO)=1.40~2.00 and (K2 O+Li 2 O+Na 2 O+B 2 O 3 ) / (SiO 2 +Al 2 O 3 )=0.10~0.20,Al 2 O 3 / SiO 2 =0.50~0.80,Li 2 O / (K 2 O+Li 2 O+Na 2 O)=0.25~0.85,Li 2 O+Na 2 O≥7.00mol%, the heat treatment temperature required for preparing the target glass-ceramics can be reduced, and transparent zinc-magnesium spinel glass-ceramics with high intrinsic strength can be prepared under the condition of heat treatment temperature below 800°C, which improves the mass production of transparent spinel glass-ceramics and ensures that the target glass-ceramics have excellent optical properties. At the same time, the glass-ceramics of the present invention has a high Young's modulus and hardness, and the glass-ceramics can be chemically strengthened to produce a strengthened glass-ceramics with excellent anti-drop performance.
[0111] In a second aspect, the present invention provides a method for preparing the above-mentioned microcrystalline glass, comprising the following steps:
[0112] (1) Preparation of substrate glass: The substrate glass contains the following oxide components in molar percentage: SiO 2 :38.00%~50.00%,Al 2 O 3 :25.00%~30.00%, MgO:4.00%~8.00%, ZnO:8.00%~14.00%, ZrO 2 :3.00%~5.00%,Li 2 O: 3.00% to 8.00% (8.00 mol %) is not taken;
[0113] Furthermore, the substrate glass does not contain TiO 2 ;
[0114] Wherein, the oxide component content of the substrate glass satisfies the following relationship:
[0115] Al 2 O 3 / (MgO+ZnO)=1.40~2.00;
[0116] (K 2 O+Li2 O+Na 2 O+B 2 O 3 ) / (SiO 2 +Al 2 O 3 )=0.10~0.20;
[0117] (2) Preparation of glass-ceramics: The substrate glass obtained in step (1) is heat-treated to obtain the above-mentioned glass-ceramics.
[0118] In some preferred embodiments of the present invention, in step (2), the heat treatment includes a nucleation treatment and a crystallization treatment performed sequentially; the temperature of the nucleation treatment is 650-850°C, preferably 650-750°C, and the time is 0-72h, preferably 0-24h; the temperature of the crystallization treatment is 700-1000°C, preferably 700-800°C, and the time is 0.1-72h, preferably 0.1-24h.
[0119] In some preferred embodiments of the present invention, the substrate glass further contains oxide components in the following proportions, measured in molar percentage of oxides: Na 2 O: 0%~6.00%, K 2 O: 0%~3.00%, B 2 O 3 :0%~6.00%, BaO: 0%~4.00%, Y 2 O 3 :0%~2.00%,La 2 O 3 :0%~2.00%;and /
[0120] Alternatively, the oxide component content, expressed in mol%, satisfies at least one of the following relationships: Al 2 O 3 / SiO 2 =0.50~0.80; Li 2 O / (K 2 O+Li 2 O+Na 2 O)=0.25~0.85;Li 2 O+Na 2 O≥7.00mol%.
[0121] In some preferred embodiments of the present invention, the above-mentioned method for preparing glass-ceramics further comprises the following steps:
[0122] The microcrystalline glass obtained by heat treatment is subjected to chemical strengthening treatment to obtain the microcrystalline glass containing the compressive stress layer.
[0123] In a third aspect, the present invention further provides a substrate glass that can be used to prepare the above-mentioned glass-ceramics, wherein the substrate glass contains the following oxide components in terms of molar percentage of oxides: SiO 2 :38.00%~50.00%,Al 2 O 3 :25.00%~30.00%, MgO:4.00%~8.00%, ZnO:8.00%~14.00%, ZrO 2 :3.00%~5.00%,Li 2 O: 3.00% to 8.00% (8.00 mol % is not taken); and the substrate glass does not contain TiO 2 ; Wherein, the oxide component content of the substrate glass satisfies the following relationship: Al 2 O 3 / (MgO+ZnO)=1.40~2.00;(K 2 O+Li 2 O+Na 2 O+B 2 O 3 )
[0124] / (SiO 2 +Al 2 O 3 )=0.10~0.20.
[0125] In some preferred embodiments of the present invention, the substrate glass further contains oxide components in the following proportions, measured in molar percentage of oxides: Na 2 O: 0%~6.00%, K 2 O: 0%~3.00%, B 2 O 3 :0%~6.00%, BaO: 0%~4.00%, Y 2 O 3 :0%~2.00%,La 2 O 3 : 0% to 2.00%; and / or, the oxide component content is measured in mol%, satisfying at least one of the following relationships: Al 2 O 3 / SiO 2 =0.50~0.80; Li 2 O / (K 2 O+Li 2 O+Na 2 O)=0.25~0.85;Li 2 O+Na 2 O≥7.00mol%.
[0126] In the present invention, the forming method of the substrate glass includes but is not limited to float, overflow, rolling or casting process. For example, the components are mixed evenly according to the formula, melted and formed, and then cooled and annealed to obtain the substrate glass. When preparing the substrate glass, a clarifier can be added to the substrate glass, and the clarifier is not limited to SnO 2 , Sb 2 O 3 , NaCl; based on the mass of the substrate glass, the amount of the clarifier added is 0.01wt% to 2.00wt%, preferably 0.01wt% to 1.50wt%.
[0127] In a fourth aspect, the present invention also provides the use of the above-mentioned microcrystalline glass in mobile phone displays, tablet computer displays, handheld game consoles, electronic terminals, portable digital devices, vehicle central control screens, electronic whiteboard glass, smart home touch screens, vehicle windshields, aircraft windshields or aircraft windshields.
[0128] Glossary:
[0129] 1. Glass-ceramics: Also known as glass ceramics, it is a type of solid composite material that contains both glass phase and crystal phase (microcrystalline phase, crystalline phase, crystalline phase) prepared by targeted controlled heat treatment of the base glass. It should be understood that both the crystal phase and the grain refer to the crystals precipitated in the glass-ceramics, but the description methods are different.
[0130] 2. Base glass: glass that has not been subjected to nucleation treatment, crystallization treatment, or strengthening treatment.
[0131] 3. Strengthened glass-ceramics: It is a solid composite material obtained after chemical strengthening treatment of glass-ceramics. During high-temperature chemical strengthening treatment, the alkali metal ions with large ionic radius (such as potassium ions and sodium ions) in the salt bath / molten salt will replace the alkali metal ions with small ionic radius (such as sodium ions and lithium ions) in the glass-ceramics, thereby generating an exchange ion volume difference and generating compressive stress on the surface of the glass-ceramics.
[0132] 4.DOL_0: Depth of compressive stress layer, also known as depth of compressive stress layer, refers to the distance from any surface of the glass to the position close to the surface where the compressive stress is zero.
[0133] 5. |CT_AV|: The absolute value of the average tensile stress in the tensile stress layer, specifically refers to the absolute value of the average value of all tensile stresses in the tensile stress layer.
[0134] Test method:
[0135] 1. Test conditions for |CT_AV| and DOL_0: Use SLP-2000 from Orihara, Japan, with a light source wavelength of 518nm, SOC=25.5(nm / cm) / MPa, refractive index=1.60, and exposure time of 300usec. SOC is the photoelastic coefficient. Photoelasticity mainly refers to the phenomenon of anisotropy and birefringence of transparent materials after being subjected to force. By measuring the photoelastic coefficient and birefringence, the value of the residual stress (MPa) inside the material can be obtained.
[0136] 2. Glass thickness: Determined by micrometer test. The thickness change of glass-ceramics before and after chemical strengthening is very small and can be ignored.
[0137] 3. Differential Scanning Calorimetry (DSC) test: Grind the sample and pass it through a 200-mesh sieve (U.S. Taylor standard sieve); the test conditions are: room temperature ~ 1100°C, 10°C / min heating rate; the test instrument is Mettler-Toledo TGA / DSC3+ thermogravimetric and synchronous thermal analyzer.
[0138] 4. Average grain size: The microcrystalline glass sample is tested using an X-ray diffractometer. The Scherrer formula D=Kλ / (βcosθ) is used for the result data obtained from the XRD test, where λ is the X-ray wavelength of 0.154056nm, β is the peak half-height width, and K=0.89 to obtain the average grain size. The X-ray diffractometer used in the present invention is Shimadzu XRD-6100, the target material is copper, the test incident angle range is 2θ=10-80°, the scanning speed is 6° / min, the operating voltage is 40KV, and the operating current is 30mA.
[0139] 5. Optical performance test: According to the standard of GB / T 7962.12-2010 Test method for colorless optical glass Part 12: Spectral transmittance, use professional testing instruments to test the transmittance, a* value, and b* value of microcrystalline glass. The testing instrument used in the present invention is the Konica Minolta Spectrophotometer CM-3600A from Japan.
[0140] 6. Crystallinity test: Use an X-ray diffractometer to test the glass-ceramic sample to obtain an XRD diffraction peak curve, then import the X-ray diffractometer test result file (RAW format) into the X-ray diffraction data Rietveld refinement software (such as Gsas, Fullprof, or Maud), perform fitting and calculation, and then obtain the crystallinity of the glass-ceramic sample. The ratio of the fitted crystal phase peak area to the fitted total peak area is the crystallinity. The X-ray diffractometer used in the present invention is Shimadzu XRD-6100, the incident angle range used in the test is 2θ=10-80°, the scanning speed is 6° / min, the operating voltage is 40KV, and the operating current is 30mA.
[0141] 7. Average sandpaper drop resistance height: The value obtained by dividing the sum of the sandpaper drop resistance heights measured for multiple glass samples by the number of samples measured, which is used to characterize the drop resistance performance of microcrystalline glass.
[0142] Take at least 10 samples from each batch for testing, and the average sandpaper drop resistance height is:
[0143]
[0144] Where n is the number of glass samples tested in each batch, and hi is the sandpaper drop resistance height of a single sample tested.
[0145] Among them, the test method for the sample's resistance to sandpaper drop height is:
[0146] Step 1: Stick 80-grit sandpaper on the lower surface of the 160g model machine, and place the model machine on the green figure LT-SKDL-CD drop machine.
[0147] Step 2: Place a glass sample to be tested with a length, width and thickness of 50mm*50mm*0.7mm directly under the model machine, with the glass sample facing the sandpaper. Make the model machine fall from a certain drop height to impact the glass sample directly under the model machine. If the glass sample does not break, the drop height of the model machine is increased according to a certain rule. For example, the drop height starts from 0.4m, and the sample is dropped once. If it does not break, increase the height by 0.1m each time and drop again until the glass sample breaks.
[0148] Step 3: The last drop height of the glass sample when it breaks is recorded as the anti-sandpaper drop height. For example, if the drop height when it breaks is 0.5m, the anti-sandpaper drop height of the sample is 0.4m.
[0149] 8. Vickers hardness test: The strengthened microcrystalline glass sheet is made into a small piece of 50mm*50mm*0.7mm, and a glass sample with a clean surface and no visible scratches, pits, cracks and other damage is selected as a sample, and then the Vickers hardness is measured using a Vickers hardness tester. Three different positions are selected on the surface of the same sample for measurement, and then the average value is taken as the final test result. The Vickers hardness tester used in the present invention is a digital display small load Vickers hardness tester (Beijing Kewei Technology Co., Ltd., VTD405), with a load of 300gf, a load time of 10s, and the validity of the indentation complies with GB / T 16534.
[0150] 9. Measurement of Young's modulus: Young's modulus E is a value measured by a known resonance method.
[0151] 10. Fracture toughness test: The test method refers to the Vickers hardness test method, using the formula
[0152]
[0153] The fracture toughness value is calculated, where E is Young's modulus, in GPa; Hv is Vickers hardness, in GPa (1 GPa = 102.04 Hv); P is load, in Kg; and C is the average crack length.
[0154] 11. Refractive index test: The present invention uses a monocular Abbe refractometer (WYA-2WAJ, Bell Analytical Instruments Co., Ltd.) and sets the wavelength to 589 nm to test the refractive index of the microcrystalline glass sheet.
[0155] The glass-ceramics of the present invention will be described in detail below through specific embodiments.
[0156] Example
[0157] 1. Melting substrate glass:
[0158] 1000 g of raw materials were prepared according to the formula shown in Tables 1A, 1B and 1C as raw materials for preparing substrate glass, and then mixed in a V-type mixer for 30 minutes. After mixing, 5 g of clarifier (NaCl) was added, and then the raw materials were transferred to a platinum crucible, and then melted in a 1650°C lifting furnace for 5 hours, and then poured into a molding mold for molding and cooling. After cooling to 900°C, it was then placed in a 600°C annealing furnace for annealing for 24 hours, and then cooled to room temperature with the furnace to obtain substrate glasses D1-D10 and S1-S17.
[0159] 2. Heat treatment of substrate glass to prepare glass-ceramics:
[0160] The substrate glass is subjected to the heat treatment process R shown in Table 2. 1 -R 10 The substrate glasses D1-D10 and S1-S17 of step (i) are heat treated in turn under the parameter conditions shown in the table to obtain glass-ceramics bricks. The specific heat treatment processes of various substrate glasses and the obtained glass-ceramics states are shown in Tables 3A, 3B, 3C and 3D. Tables 3A-3D show the glass-ceramics of experimental numbers 1-35.
[0161] 3. Sample processing:
[0162] After shaping, cutting and polishing, the glass-ceramic sample bricks can be obtained into samples of desired size, such as a glass-ceramic sample with a length, width and thickness of 50mm*50mm*0.7mm.
[0163] 4. Chemically strengthen the glass-ceramics to prepare glass-ceramics containing a compressive stress layer (also known as strengthened glass-ceramics):
[0164] The glass-ceramics sample obtained in step (iii) is chemically strengthened in a strengthening salt bath of the composition and strengthening temperature and time conditions shown in Tables 4A-4C, thereby obtaining strengthened glass-ceramics. The sodium ions in the salt bath are provided by sodium nitrate, and the potassium ions are provided by potassium nitrate. Specifically, the salt bath composition in Tables 4A-4C is specifically a salt bath consisting of only sodium nitrate for strengthening or a salt bath consisting of a mixture of sodium nitrate and potassium nitrate for strengthening, wherein, when the salt bath is composed of a mixture of sodium nitrate and potassium nitrate, the mass concentration of sodium nitrate is in the range of 30-100wt%, and specifically can be 30-70wt%.
[0165] The physical properties of each strengthened glass-ceramic after specific chemical strengthening are shown in Tables 4A-4C.
[0166] in addition, Figure 1 The DSC test curve of the substrate glass D3 shows that its nucleation temperature is about 778°C and the crystallization starting temperature is about 905°C. Figure 2 The DSC test curve of the substrate glass D4 shows that its nucleation temperature is about 918°C and the crystallization starting temperature is about 958°C. Figure 3 The DSC test curve of the substrate glass S3 shows that its nucleation temperature is about 735°C and the crystallization starting temperature is about 760°C; Figure 4 The DSC test curve of the substrate glass S5 shows that its nucleation temperature is about 700°C and the crystallization starting temperature is about 735°C. Figure 5 This is a photo of the brick of the substrate glass D1. Due to the high Zr content, there is a lot of white precipitate on the surface of the substrate glass after melting; Figure 6 This is the glass-ceramic sample image corresponding to Experiment No. 3. It can be seen that due to the high Li content in the composition, a quartz solid solution (MgAl) appeared in the glass-ceramic after crystallization. 2 Si 3 O 10 ) crystals, resulting in overall devitrification of the glass-ceramics; Figure 7 This is the XRD test curve of the glass-ceramics corresponding to Experiment No. 19. It can be seen that the crystals are complete and there is no impurity phase. Figure 8 This is the picture of the glass-ceramic sample corresponding to experiment number 18. It can be seen that due to the low Al content, a small amount of quartz crystals appeared after crystallization, which manifested as fogging of the sample.
[0167] Table 1A Glass formula and melting state (I)
[0168]
[0169] Table 1B Glass formula and melting state (II)
[0170]
[0171] Table 1C Glass formula and melting state (III)
[0172]
[0173] According to the data in Tables 1A-1C above, it can be seen that the substrate glass D1 has ZrO 2 The content is too high, and a large amount of white precipitation appears after melting; the substrate glass D4 contains TiO 2 , the whole is yellow after melting; the base glass D5 is due to Al 2 O 3 The content is too high, and there is a lot of unmelted material during melting; the base glass D8 has Na 2 The O content is too high and it has become ceramic after annealing; the melting of other formulas is normal.
[0174] Table 2 Heat treatment process parameters
[0175]
[0176] Table 3A Heat treatment process and glass-ceramic state results (I)
[0177]
[0178] Table 3B Heat treatment process and glass-ceramic state results (II)
[0179]
[0180] Table 3C Heat treatment process and glass-ceramic state results (III)
[0181]
[0182] Table 3D heat treatment process and glass-ceramic state results (IV)
[0183]
[0184] As above: D2 due to Li 2 O content is too high, and quartz solid solution (MgAl 2 Si 3 O 10 ), causing the glass to become foggy or even ceramicized. Ceramics here refers to the uncontrollable growth of quartz crystals during heat treatment of microcrystalline glass, causing the sample to lose the transparent properties of glass and become white similar to ceramics, such as Figure 6 ; D3 in R 2 Only ZrO under heat treatment conditions 2 Crystalline phase precipitation, without the desired zinc-magnesium spinel solid solution, at a higher temperature of 850℃-4h (R 3, crystallization treatment at 850℃), the crystallinity is only 17.6wt%. 8 , crystallization treatment was carried out at 850℃, and nucleation process was also carried out before crystallization treatment), the crystallinity was only 18.3wt%. Only when high temperature heat treatment was carried out (R4, crystallization treatment was carried out at 900℃), a sample with good crystallization state could be obtained, and the crystallinity reached 35.7wt%. D4 contained some TiO 2 , turns brown after heat treatment; D6 due to ZrO 2 The content is too low, and fogging occurs after heat treatment, but the specific reason cannot be found from the XRD parameters. It is speculated from the literature that the fogging may be caused by the aggregation of small grains; D7 obtained transparent microcrystalline glass. D9 due to B 2 O 3 The content is high and it becomes foggy after heat treatment. The reason may be due to phase separation, and no difference can be found from the XRD parameters. 2 O 3 The content is low, and after crystallization, there is a quartz solid solution (MgAl 2 Si 3 O 10 ) appears, the sample becomes foggy, such as Figure 8 .
[0185] Table 4A Physical properties and strengthening parameters (I)
[0186]
[0187] Table 4B Physical properties and strengthening parameters (II)
[0188]
[0189] Table 4C Physical properties and strengthening parameters (III)
[0190]
[0191] As mentioned above, in Experiment No. 8, due to the substrate glass Al 2 O 3 The content is low, and the stress obtained by chemical strengthening of glass-ceramics is poor. In experiment No. 12, since the substrate glass contains TiO 2 , the a*(D65) and b*(D65) values of the glass-ceramics are both high, and the optics are poor; in experiment number 15, due to the substrate glass Li 2 The O content is low, and the deep stress level obtained after strengthening the microcrystalline glass is low, and the depth of the compressive stress layer is less than 95μm; in experiment No. 17, due to the substrate glass B 2 O 3Too high a content leads to phase separation during heat treatment, and the transmittance of the microcrystalline glass is poor; in experiment numbers 19 to 35, the microcrystalline glass has excellent optical properties and deep stress levels after chemical strengthening, and has good drop resistance. The test was carried out using 80-grit sandpaper, and the average sandpaper drop resistance height was above 1.0m.
Claims
1. A strengthened glass-ceramic, characterized in that: The strengthened microcrystalline glass comprises a compressive stress layer and a tensile stress layer; the strengthened microcrystalline glass contains (Zn, Mg)Al2O4 as the main crystalline phase and secondary crystalline tetragonal ZrO2; The composition of the tensile stress layer of the strengthened glass-ceramics, measured in molar percentage of oxides, comprises: Furthermore, the strengthened glass-ceramics substantially does not contain TiO2; the Li2O does not take 8.00 mol%; Wherein, in terms of the molar percentage of oxides, the composition of the tensile stress layer of the strengthened glass-ceramics satisfies the following relationship: (1)Al2O3 / (MgO+ZnO)=1.40~2.00; (2) (K2O+Li2O+Na2O+B2O3) / (SiO2+Al2O3)=0.10~0.20; Each oxide in the above relationship represents the mole percentage content of the oxide in the component.
2. The tempered glass-ceramics according to claim 1, characterized in that: Calculated by molar percentage of oxides, in the tensile stress layer of the strengthened microcrystalline glass, the molar percentage of SiO2 is 38.50% to 48.50%, preferably 40.00% to 46.50%; and / or the molar percentage of Al2O3 is 25.00% to 29.00%, preferably 25.50% to 27.50%; and / or the molar percentage of MgO is 4.50% to 7.50%, preferably 4.50% to 6.00%; and / or the molar percentage of ZnO is 8.50% to 13.50%, preferably 9.00% to 11.00%; and / or the molar percentage of ZrO2 is 3.00% to 4.50%, preferably 3.00% to 4.00%; and / or the molar percentage of Li2O is 3.00% to 7.80%, preferably 4.50% to 7.50%.
3. The tempered glass-ceramics according to claim 1 or 2, characterized in that: The composition of the tensile stress layer of the strengthened glass-ceramics, measured in molar percentage of oxides, further comprises:
4. The tempered glass-ceramics according to any one of claims 1 to 3, characterized in that: The content of the oxide component is expressed in mol%, and the composition of the tensile stress layer of the strengthened microcrystalline glass satisfies at least one of the relations (3), (4) and (5): (3)Al2O3 / SiO2=0.50~0.80; (4)Li2O / (K2O+Li2O+Na2O)=0.25~0.85; (5) Li2O+Na2O≥7.00mol%.
5. The tempered glass-ceramics according to any one of claims 1 to 4, characterized in that: Calculated in terms of molar percentage of oxides, in the tensile stress layer of the strengthened microcrystalline glass, the molar percentage of Na2O is 2.5% to 4.0%; and / or, the molar percentage of K2O is 0% to 1.00%; and / or, the molar percentage of B2O3 is 0% to 2.0%; and / or, the molar percentage of BaO is 0.5% to 2.5%; and / or, the molar percentage of Y2O3 is 0% to 1.0%; and / or, the molar percentage of La2O3 is 0% to 1.0%.
6. The tempered glass-ceramics according to any one of claims 1 to 5, characterized in that: The weight ratio of the crystal phase of the strengthened glass-ceramics to the strengthened glass-ceramics is 25.0-45.0wt%, preferably 30.0-45.0wt%, and more preferably 32.0-40.0wt%.
7. The tempered glass-ceramics according to any one of claims 1 to 6, characterized in that: The average grain size of the strengthened glass-ceramics is 3.0-30.0 nm, preferably 5.0-6.5 nm, and more preferably 5.2-6.5 nm.
8. The tempered glass-ceramics according to any one of claims 1 to 7, characterized in that: The Young's modulus of the strengthened glass-ceramics is ≥110 GPa, preferably, 130 GPa ≥ Young's modulus ≥110 GPa, and more preferably, 130 GPa ≥ Young's modulus>114 GPa.
9. The tempered glass-ceramics according to any one of claims 1 to 8, characterized in that: When the thickness is 0.7 mm, the strengthened microcrystalline glass has the following transmission color coordinates in the CIELAB color space: a*=-0.15 to 0.15, preferably, a*=0.15 to -0.03; and b*=0.30 to 0.90, preferably b*=0.60 to 0.85; this is for D65 light source in SCI mode.
10. The tempered glass-ceramics according to any one of claims 1 to 9, characterized in that: When the thickness is 0.7 mm, the transmittance of the strengthened microcrystalline glass under light of 550 nm wavelength is above 85.0%, preferably, the transmittance is 88.0%-95.0%; when the thickness is 0.7 mm, the transmittance of the strengthened microcrystalline glass under light of 360 nm wavelength is above 70.0%.
11. The strengthened glass-ceramics according to any one of claims 1 to 10, characterized in that: The depth of the compressive stress layer of the strengthened microcrystalline glass is DOL_0≥0.14t, where t is the thickness of the microcrystalline glass, and preferably, 0.20t≥DOL_0≥0.15t.
12. The tempered glass-ceramics according to any one of claims 1 to 11, characterized in that: The |CT_AV| of the strengthened glass-ceramics is ≥40.0MPa, preferably, 80.0MPa≥|CT_AV|≥40.0MPa.
13. The strengthened glass-ceramics according to any one of claims 1 to 12, characterized in that: The strengthened glass-ceramics are obtained by chemical strengthening treatment in a salt bath containing potassium salt and / or sodium salt, wherein the salt bath contains 0-1wt% of lithium salt; preferably, the strengthened glass-ceramics are obtained by chemical strengthening treatment in a mixed salt bath of sodium salt and potassium salt or a pure sodium salt bath; more preferably, the strengthened glass-ceramics are obtained by chemical strengthening treatment in a mixed salt bath of sodium nitrate and potassium nitrate or a sodium nitrate salt bath, preferably, in the mixed salt bath of sodium nitrate and potassium nitrate, the sodium nitrate concentration is 30-70wt%.
14. The strengthened glass-ceramics according to any one of claims 1 to 13, characterized in that: The Vickers hardness of the strengthened glass-ceramics is above 750 HV. And / or, the fracture toughness of the strengthened glass-ceramics is 1.200 MPa·m 1 / 2 More than, preferably, the fracture toughness is 1.400 MPa·m 1 / 2 More preferably, the fracture toughness is 1.500 MPa·m 1 / 2 above.
15. The tempered glass-ceramics according to claim 1 or 2, characterized in that: In terms of molar percentage of oxides, the composition of the tensile stress layer of the strengthened microcrystalline glass comprises: 45.28%, 45.58%, 44.01%, 46.53%, 39.21%, 45.68%, 38.76%, 45.12%, 44.98%, 45.36%, 46.03%, 44.79%, 48.11%, 45.23% or 43.40% SiO2; and / or, 25.91%, 25.36%, 26.62%, 28.31%, 26.34%, 29.15%, 25.43%, 25.93%, 25.96%, 26.35%, 25.00%, 26.09%, 25.40%, 25.38%, 25.88% or 25.15% Al2O3; and / or, 3.54%, 3.57%, 4.29%, 3.64%, 3.36%, 4.45%, 3.32%, 4.30%, 4.38%, 3.55%, 3.60%, 3.44%, 3.50%, 3.34% or 3.79% ZrO2; and / or, 5.91%, 5.95%, 4.21%, 6.07%, 5.61%, 4.37%, 5.54%, 7.65%, 5.85%, 5.92%, 6.01%, 5.74%, 5.57%, 5.90% or 5.69% MgO; and / or, 10.14%, 10.21%, 13.49%, 8.37%, 9.62%, 10.20%, 9.51%, 8.85%, 10.04%, 10.16%, 10.32%, 9.86%, 10.03%, 9.55%, 10.13% or 9.77% ZnO; and / or, 1.58%, 3.57%, 3.43%, 3.64%, 3.02%, 2.98%, 3.44%, 3.51%, 1.58%, 1.61%, 5.36%, 5.55%, 4.47%, 1.49% or 3.41% Na2O; and / or, 5.97%, 5.03%, 3.88%, 5.13%, 4.15%, 4.02%, 4.10%, 3.96%, 5.99%, 6.08%, 3.12%, 3.05%, 3.21%, 5.63%, 7.74% or 3.86% Li2O; and / or, 0.00%, 0.19%, 5.60%, 5.53%, 0.93% or 3.79% B2O3.
16. The strengthened glass-ceramics according to any one of claims 1 to 15, characterized in that: At a thickness of 0.7 mm, the tempered glass-ceramics is subjected to a sandpaper drop resistance test using 80-mesh sandpaper, and the average sandpaper drop resistance height of the tempered glass-ceramics is greater than or equal to 0.8 m. Preferably, the average sandpaper drop resistance height of the tempered glass-ceramics is 1.00-1.60 m.
17. A method for preparing strengthened glass-ceramics, characterized in that: The steps include: (1) Preparation of substrate glass: The substrate glass contains the following oxide components in molar percentage: SiO2: 38.00% to 50.00%, Al2O3: 25.00% to 30.00%, MgO: 4.00% to 8.00%, ZnO: 8.00% to 14.00%, ZrO2: 3.00% to 5.00%, Li2O: 3.00% to 8.00% (not 8.00 mol%), Na2O: 0% to 6.00%, B2O3: 0% to 6.00%; and the substrate glass does not contain TiO2; Wherein, the oxide component content of the substrate glass satisfies the following relationship: Al2O3 / (MgO+ZnO)=1.40~2.00; (K2O+Li2O+Na2O+B2O3) / (SiO2+Al2O3)=0.10~0.20; (2) Preparation of glass-ceramics: heat-treating the substrate glass obtained in step (1) to obtain glass-ceramics, and then chemically strengthening the heat-treated glass-ceramics to obtain the strengthened glass-ceramics as described in any one of claims 1 to 16.
18. The preparation method according to claim 17, characterized in that: In the step (2), the heat treatment includes a nucleation treatment and a crystallization treatment performed sequentially; the temperature of the nucleation treatment is 650-850°C, and the time is 0-72h, preferably, the temperature of the nucleation treatment is 650-750°C, and the time is 0-24h; the temperature of the crystallization treatment is 700-1000°C, and the time is 0.1-72h, preferably, the temperature of the crystallization treatment is 700-800°C, and the time is 0.1-24h.
19. The preparation method according to claim 17 or 18, characterized in that: In the step (2), the salt bath used for chemical strengthening treatment is a salt bath containing potassium salt and / or sodium salt, wherein the salt bath contains 0-1wt% of lithium salt. Preferably, the salt bath used for chemical strengthening treatment is a mixed salt bath of sodium salt and potassium salt or a pure sodium salt bath. More preferably, the salt bath used for chemical strengthening treatment is a mixed salt bath of sodium nitrate and potassium nitrate or a sodium nitrate salt bath. Preferably, in the mixed salt bath of sodium nitrate and potassium nitrate, the concentration of sodium nitrate is 30-70wt%.
20. The preparation method according to any one of claims 17 to 19, characterized in that: The substrate glass further contains oxide components in the following proportions, measured in molar percentage of oxides: Na2O: 0.5% to 5.50%, K2O: 0% to 3.00%, B2O3: 0% to 6.00%, BaO: 0% to 4.00%, Y2O3: 0% to 2.00%, La2O3: 0% to 2.00%; and / or, the content of the oxide components, measured in mol%, satisfies at least one of the following relationships: Al2O3 / SiO2=0.50 to 0.80; Li2O / (K2O+Li2O+Na2O)=0.25~0.85; Li2O+Na2O≥7.00mol%.
21. An electronic terminal, characterized in that: The electronic terminal comprises the strengthened glass-ceramic according to any one of claims 1 to 16.
22. A display screen, characterized in that: The display screen comprises the strengthened micro-ceramic glass according to any one of claims 1 to 16.
23. The display screen according to claim 23, characterized in that: The display screen includes a mobile phone display screen, a tablet computer display screen, a vehicle central control screen or a smart home touch screen.
24. A windshield, characterized in that: The windshield comprises the strengthened micro-ceramic glass according to any one of claims 1 to 16.
25. The windshield according to claim 25, characterized in that: The windshield includes a vehicle windshield, an aircraft windshield or an aircraft windshield.
26. Use of the tempered micro-ceramic glass according to any one of claims 1 to 16 in mobile phone displays, tablet computer displays, handheld game consoles, electronic terminals, portable digital devices, vehicle central control screens, electronic whiteboard glass, smart home touch screens, vehicle windshields, aircraft windshields or aircraft windshields.
Citation Information
Patent Citations
Nano-scale spinel glass ceramic and preparation method thereof
CN104478219A
Spinel transparent microcrystalline glass with low melting temperature, preparation method and performance enhancing method thereof
CN111018354A
Glass-ceramics
US5968857A